THE TRANSPORT OF UZBEKISTAN SSR AND ITS ROLE IN THE ECONOMY OF THE SOVIET GOVERNMENT (Scientific journal of the Fergana State University, 2024)
In this article, information about the role and importance of the transport system of the Uzbek SSR during the Soviet regime is studied based on the analysis of sources and literature. This study is of great importance in determining the state of the country's transport system during the colonial period and the goals of its development. For this purpose, it was studied how the transport system organized by the Center was organized in the interest of the people and what results were achieved during this process. During the research, it was determined based on the sources that during the colonial period, the transport of Uzbekistan was mainly a means of serving the needs of the Center, and that this system was established for the development of a one-sided economy. In addition, the reforms in the issue of providing the population with vehicles during the colonial period, their achievements and shortcomings are also covered in detail. In addition, the issue of transportation by means of vehicles was evaluated analytically and critically at the national and international level. Opinions about infrastructure activity related to network activity are presented. This research can be used in educational institutions in the field of transport.